Odpowiedź:
[tex]a)\\\\6(2x-2)=3(-x+5)\\\\12x-12=-3x+15\\\\12x+3x=15+12\\\\15x=27\ \ |:15\\\\x=\frac{27}{15}\\\\x=\frac{9}{5}\\\\x=1\frac{4}{5}\\\\\\b)\\\\\frac{x}{3}+2=\frac{2}{3}x+2\frac{1}{3}\\\\\frac{x}{3}+2=\frac{2}{3}x+\frac{7}{3}\ \ |\cdot3\\\\x+6=2x+7\\\\x-2x=7-6\\\\-x=1\ \ |\cdot(-1)\\\\x=-1[/tex]
[tex]c)\\\\3-(5x-3)=2-(x+1)\\\\3-5x+3=2-x-1\\\\6-5x=1-x\\\\-5x+x=1-6\\\\-4x=-5\ \ |:(-4)\\\\x=\frac{5}{4}\\\\x=1\frac{1}{4}\\\\\\d)\\\\\frac{7}{9}(y+2)=\frac{7}{9}\ \ |:\frac{7}{9}\\\\y+2=1\\\\y=1-2\\\\y=-1\\\\\\e)\\\\\frac{x+3}{2}-(1-y)=3,5\\\\\frac{x+3}{2}-1+y=3,5\ \ |\cdot2\\\\x+3-2+2y=7\\\\x+1+2y=7\\\\x=7-1-2y\\\\x=6-2y[/tex]
[tex]f)\\\\0,7(x+2)=0,3x-1\\\\0,7x+1,4=0,3x-1\\\\0,7x-0,3x=-1-1,4\\\\0,4x=-2,4\ \ |:0,4\\\\x=-6\\\\\\g)\\\\0,4x+2,3=1,2x-2,5\\\\0,4x-1,2x=-2,5-2,3\\\\-0,8x=-48\ \ |:(-0,8)\\\\x=6[/tex]